Editorial. Issue 3 (11th October 2018) - van der Spek, Ad J.F.; van den Berg, Niels
Abstract : The Wadden Sea region spans a distance of nearly 500km along the North Sea coast from the Netherlands to Denmark. It consists of a chain of barrier islands which shelter an area of extensive intertidal flats and salt marshes that are dissected by tidal channels and creeks. Moreover, several estuaries are part of this area which is known for its intriguing morphodynamics. The natural process of continuous erosion, transport and deposition of sediment shapes the morphology of the area, which has a high ecological value, especially the intertidal morphology that supports a wide range of wildlife.